P05.07 Neisseria gonorrhoeae multiantigen sequence typing (ng-mast) of isolates collected from std patients in delhi, india. (13th September 2015) - Sood, S; Mahajan, N; Singh, R; Kapil, A; Das, BK; Sreenivas, V; Kar, HK; Sharma, VK
Abstract : Background: Neisseria gonorrhoeae multiantigen sequence typing (NG-MAST) is a highly discriminatory technique for assessing the genetic diversity of N. gonorrhoeae and has also been put forward as a tool for predicting specific antimicrobial resistance (AMR) phenotypes. Therefore, the present study was undertaken to investigate the molecular epidemiology of N. gonorrhoeae isolates using NG-MAST in Delhi and to examine if it can be used as a means for predicting AMR. This is the first such research performed in this country. Methods: 100 consecutive gonococcal isolates between April 2010 to October 2013 were investigated. Antimicrobial susceptibility testing was done using disc diffusion method and E test and the results interpreted using the breakpoint criteria of CDS technique. NG-MAST was performed as described previously. WHO N. gonorrhoeae reference strains F, G, K-P were used as controls. Association between NG-MAST sequence type (ST) and antimicrobial susceptibility was probed using chi-square and fisher's exact tests. Results: Rates of resistance to classical antibiotics were high. Decreased susceptibility to ceftriaxone (MIC 0.032–0.25 µg/ml) was demonstrated in 5% while azithromycin resistance (MIC ≥1 µg/ml) was seen in 4% isolates. N. gonorrhoeae isolates were assigned into 60 different STs and 43 (71.6%) have not been reported previously to the international database. The most common ST was 6058 (21%), followed by ST 9774 (4%), ST9875 (4%), ST9783 (4%) and ST2990 (3%). The majority of the STs (76.6%) were represented by a single isolate. There was significant association between ST6058 and resistance to penicillin (p = 0.00) and tetracycline (p = 0.002). In all the other antibiotics, no association was found. Conclusion: Our work reflects a highly diversified gonococcal population in Delhi. Further, NG-MAST has a limited applicability as a tool for predicting AMR in our region. A detailed investigation on a large number of representative isolates may provide insight into sexual networks in the city. Disclosure of interest statement: None.